Climate change and growth in Asia - Hossain, Moazzem, 1950-; Selvanathan, E. Antony, 1954-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2011)
Climate Change and Growth in Asia is a comprehensive analysis of the major issues of climate change and global warming and their possible impacts on the growth of major Asian economies. The book addresses the climate change crisis in Asia within the context of three major challenges to growth: population, poverty and greenhouse gas emissions.
Population, Poverty and CO2 Emissions in Asia : An Overview / Moazzem Hossain and Antony Selvanathan -- The Production of Biofuels : Welfare and Environmental Consequences for Asia / Clem Tisdell -- Climate Change and Freshwater Resources of Bangladesh / Qazi Kholiquzzaman Ahmad -- Analyses of Livelihoods in the Bay of Bengal Delta / A.H.M. Ali, Antony Selvanathan, and Moazzem Hossain -- Greenhouse Gas Abatement in Asia : Imperatives, Incentives and Equity / Colin Hunt -- Climate Change Impacts and Adaptation Strategies for Bangladesh / M.H. Rahman, M.A. Noor, and A. Ahmed -- Climate Change, Vulnerabilities and South Asia : Issues, Challenges and Options / M. Adil Khan -- Harmony in China's Climate Change Policy / Paul Howard -- Managing Businesses in Uncertain Times : Sustainable Development and an Ensemble Leadership Repertoire / Vikram Murthy -- Climate Change and Human Security Issues in the Asia-Pacific Region / Malcolm McIntosh and Tapan Sarker -- Media Framing of Public Discourse on Climate Change and Sea Level Rise : Social Amplification of Global Warming versus Climate Justice for Global Warming Impacts / Harun Rashid.
Includes bibliographical references and index.
Keywords: Climatic changes -- Economic aspects -- Asia; Economic development -- Asia; Climatic changes -- Government policy -- Asia; Environmental policy -- Economic aspects -- Asia; Asia -- Economic conditions -- 21st century; Electronic books